A retrospective study on the effects of sglt2 inhibitors on left ventricular function and heart failure hospitalization among heart failure with reduced ejection fraction in HUSM patients - Ramli, Siti Alis Solihan (2023)
Background: Heart failure is a worldwide concern, and multiple measures are taken to treat heart failure. Using sodium glucose like co-transporter 2 inhibitor (SGLT2i) has shown clinical benefit in reducing the risk of heart failure hospitalization and mortality. However, the effect of SGLT2i on the left ventricular function and heart failure hospitalization in heart failure patients with reduced ejection fraction (HFrEF) in this country is unclear. Objective: To determine the effect of SGLT2i (empaglifozin and dapaglifozin) on left ventricular function and heart failure hospitalization in HFrEF patients. Materials and Methods: This retrospective cohort study was conducted from December 2022 until February 2023 in Hospital USM. The data of patients who attended the cardiology and heart failure clinic from 2018 to 2022, with left ventricular ejection fraction (LVEF) ≤ 40%, were retrieved. The patients were divided into two groups based on the received treatment: with SGLT2i and without SGLT2i. The echocardiography data at baseline and after six months up to 24 months also obtained from medical records. The primary endpoint was the changes in LVEF and hospitalization for heart failure. Additionally, factors associated with LVEF changes and admission to the hospital were also determined. Results: A total of 110 HFrEF were included in the study. After a median of 14.5 (SGLT2i) and 13.3 months (non-SGLT2i) of follow-up, there was an improvement of left ventricular function in both groups. A 5.6 % improvement of LV function was observed in SGLT2i groups while 4.6% improvement was observed in non-SGLT2i group. Heart failure (HF) patients receiving SGLT2i have a lower risk of hospitalization for heart failure. Among 55 patients on SGLT2i, 20% (11 patients) had been admitted for heart failure, while 38.2% (21 patients) were not on SGLT2i admitted for heart failure with a significant p-value 0.036. The odds of being admitted in patient who did not receive SGLT2i was 2.7. This study also found out that HF patients who received oral furosemide had the odds of being admitted for heart failure at 3.512 compared to those who did not. Conclusions: SGLT2i (empaglifozin and dapagliflozin) reduces heart failure hospitalization when added into prescribed standard heart failure therapy. Patients who were on standard heart failure therapy shows significant improvement in LVEF after more than 13.3 months. however, After multivariate analysis, this study also found that oral furosemide was associated with an increased risk of hospitalization.